2017
DOI: 10.1002/jcp.26186
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA LINC00968 acts as oncogene in NSCLC by activating the Wnt signaling pathway

Abstract: Long non-coding RNAs (lncRNAs) have played critical roles in a variety of cancers, including non-small cell lung cancer (N SCLC). In our study, we focused on the biological function and clinical significance of lncRNA LINC00968 in NSCLC. It was indicated that LINC00968 was significantly increased in LUAD tissues, LUSC tissues and NSCLC cells compared to their corresponding controls. Inhibition of LINC00968 was able to repress NSCLC growth, migration, and invasion in vitro while upregulation of LINC00968 revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 32 publications
(33 reference statements)
3
55
1
Order By: Relevance
“…It was predicted that STAT3 can be provided as an miR-506 target. [23][24][25] LncRNA ILF3-AS1 can promote melanoma development through targeting miR-200b/a/429. LncRNAs are transcripts with more than 200 nucleotides and show no protein-coding capacity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was predicted that STAT3 can be provided as an miR-506 target. [23][24][25] LncRNA ILF3-AS1 can promote melanoma development through targeting miR-200b/a/429. LncRNAs are transcripts with more than 200 nucleotides and show no protein-coding capacity.…”
Section: Discussionmentioning
confidence: 99%
“…21 They are manifested to be involved in biological processes. [23][24][25] LncRNA MLLT4 antisense RNA 1 is decreased and can act as a potential indicator of poor prognosis in GC. [23][24][25] LncRNA ILF3-AS1 can promote melanoma development through targeting miR-200b/a/429.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteoglycans have an indispensable role in the tumor microenvironment, and as a result, many studies have described their potential use as target genes, biomarkers, and active agents . Moreover, it has been found that mutations in cell cycle genes can affect the differentiation of squamous cells in the course of modern anticancer treatment research . Pathways in cancer, which describes important signaling pathways such as Wnt signaling and T‐cell receptor signaling, is also an important factor in the progression of NSCLC and development of squamous cell carcinoma of the lung …”
Section: Discussionmentioning
confidence: 99%
“…LINC00672 amplification (3-8%) ERBB2 endometrial cancer [36] LINC00968 amplification (4-13%) ERBB2 non-small cell lung cancer [37] LINC01132 amplification (4-24%) GATA3, cMYC, ZNF217 TP53, FGFR, ERBB2, cMYC mir-31…”
Section: Smg7-as1 Amplification (3-21%) Tp53 Fgfr Erbb2mentioning
confidence: 99%